(untitled) (Majalah Kedokteran Bandung, 2022)
Chronic exposure to insecticides, even at low levels, has led to chronic neurotoxicity. Adolescent brain is still undergoing important developments, including in the hippocampus. This study investigated neurotoxicity effects of subacute exposure to chlorpyrifos, carbofuran and cypermethrin in the brain of adolescent rats. This study was performed at the Histology, Biochemistry, and Animal House Laboratory of Jember University from November to December 2021. Subjects were divided into five groups: normal, control, chlorpyrifos, carbofuran, and cypermethrin. Short-term memory was evaluated by Y maze test and tissue damage was evaluated by histological examination. Brain MDA levels were determined by thiobarbituric acid reactive substance method to evaluate the oxidative stress effect on the organ. This study showed spontaneous alternation in the Y maze test and the number of pyramidal neurons in hippocampus decreased in the cypermethrin group. There was a significant elevation of brain MDA level in carbofuran and cypermethrin groups. Thus, cypermethrin causes more severe neurotoxicity than carbofuran and chlorpyrifos. Improvements in the insecticide application management are urgently needed to prevent neurotoxicity.